Komitmen Guru Profesional di Era Society 5.0 - Chasnah Nailah; Midayati Afifa (Universitas Pendidikan Indonesia (UPI), 2022)
Education is one of the parameters of the progress of a nation. In order to realize quality and quality education in a country, it is necessary to have supporting components in learning activities, such as educational facilities and infrastructure (adequate infrastructure), good curriculum, committed and professional educators. Teachers are role models for their students, therefore, teachers are expected to provide good examples in educating students, if teachers can carry out their obligations as educators well and skillfully, have a sense of responsibility in educating, and follow the applicable procedures. The commitment of a high teacher will always move his enthusiasm and motivation to carry out his duties and responsibilities. The teacher's commitment is his acknowledgment of the profession he is living. Professional teachers are teachers based on expertise, competence and specialist knowledge obtained through certain education. Professional teachers are qualified and qualified teachers.